2023
DOI: 10.1371/journal.pone.0285419
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and outcome of penetrating keratoplasty in bullous keratopathy post-cataract surgery vs post-glaucoma surgery

Abstract: Purpose To investigate the causes of bullous keratopathy (BK) in the Korean population and analyze the results of penetrating keratoplasty (PK) in BK eyes associated with the top two causes: pseudophakic bullous keratopathy (PBK) and glaucoma surgery-associated BK (GBK). Methods Medical records were reviewed of patients diagnosed with BK at a tertiary referral center between 2010 and 2020. The predisposing conditions, clinical characteristics and therapeutic outcomes after PK were analyzed and compared. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further analysis of the data showed that aphakic bullous keratopathy was present in 11% of the cases. A rare simultaneous occurrence of bullous keratopathy and cataracts was seen in 5% of cases [19]. Additionally, a prevalence rate of 5% for FED was discovered in the cohort under study.…”
Section: Discussionmentioning
confidence: 71%
“…Further analysis of the data showed that aphakic bullous keratopathy was present in 11% of the cases. A rare simultaneous occurrence of bullous keratopathy and cataracts was seen in 5% of cases [19]. Additionally, a prevalence rate of 5% for FED was discovered in the cohort under study.…”
Section: Discussionmentioning
confidence: 71%
“…The preferred treatment for PBK in recent years has been EK, which permits selective replacement of the host endothelium rather than PK [6]. Studies on the effectiveness of PK [7] and EK [6,8] after BK have been previously conducted. However, studies comparing the surgical results of PK and EK in PBK are lim- [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…With advancing age and a further decrease in endothelial cell density, these eyes may develop significant endothelial dysfunction and consequently pseudophakic bullous keratopathy later in life. [ 3 ]…”
mentioning
confidence: 99%